2017
DOI: 10.1016/j.bbamem.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

MPP1 directly interacts with flotillins in erythrocyte membrane - Possible mechanism of raft domain formation

Abstract: Flotillins are prominent, oligomeric protein components of erythrocyte (RBC) membrane raft domains and are considered to play an important structural role in lateral organization of the plasma membrane. In our previous work on erythroid membranes and giant plasma membrane vesicles (GPMVs) derived from them we have shown that formation of functional domains (resting state rafts) depends on the presence of membrane palmitoylated protein 1 (MPP1/p55), pointing to its new physiological role. Exploration of the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 51 publications
4
46
0
Order By: Relevance
“…Another line of data supporting a relation of flotillins with rafts come from immunofluorescence and electron microscopy studies, indicating partial co-localization of flotillins and GPI-anchored proteins after their clustering [18,35,84,94]. Moreover, recent studies of the Sikorski's group have indicated that flotillins interact with another S-palmitoylated raft-associated protein-MPP1 of the membrane-associated guanylate kinase (MAGUK) family of scaffolding proteins-and together they contribute to the assembly of rafts in the erythrocyte membrane [66,82].…”
Section: Flotillins Associate With Plasma Membrane Raftsmentioning
confidence: 96%
See 1 more Smart Citation
“…Another line of data supporting a relation of flotillins with rafts come from immunofluorescence and electron microscopy studies, indicating partial co-localization of flotillins and GPI-anchored proteins after their clustering [18,35,84,94]. Moreover, recent studies of the Sikorski's group have indicated that flotillins interact with another S-palmitoylated raft-associated protein-MPP1 of the membrane-associated guanylate kinase (MAGUK) family of scaffolding proteins-and together they contribute to the assembly of rafts in the erythrocyte membrane [66,82].…”
Section: Flotillins Associate With Plasma Membrane Raftsmentioning
confidence: 96%
“…In breast cancer cells, flotillins stabilize ErbB2 in the plasma membrane sustaining signaling activity [106]. In erythrocytes, flotillins contribute to the organization of membrane rafts in co-operation with MPP1 protein [66,82,107]. Thus, it can be proposed that flotillins bound to the inner leaflet of the plasma membrane facilitate the assembly of plasma membrane microregions originating from rafts.…”
Section: Association Of Flotillins With Rafts Facilitates Endocytosismentioning
confidence: 99%
“…Ethical approval was obtained from the ethics committees as documented previously [16,17]. Immunoreactivity screenings of plasma samples were performed by enzyme-linked immunosorbent assay (ELISA) [12] and immuno-dot blotting [18] using the synthetic peptides PfSRA P1 (NNKDNHNKKDTNENC); PfSRA P2 (CENDNDEYGNKNKNS); and PfSRA P3 (CSNNKKKKK NDKKKK). R1 peptide (LFSKFGSRMHILKC) was used as control (R1 peptide blocks AMA 1-RON 4 interaction), and naive plasma was used as negative control.…”
Section: Plasma Samples and Immunoreactivitymentioning
confidence: 99%
“…6 In a univariate analysis related to age, this study revealed no significant difference in CR between the different age groups, and the results suggest that the MIDAM regimen could be an acceptable choice as salvage treatment in the elderly. 6 In a univariate analysis related to age, this study revealed no significant difference in CR between the different age groups, and the results suggest that the MIDAM regimen could be an acceptable choice as salvage treatment in the elderly.…”
Section: Supporting Informationmentioning
confidence: 59%
“…GO in fractionated doses has been shown to be highly effective in association with chemotherapy and could be an interesting option in our MIDAM regimen because this approach allows the delivery of high cumulative doses without excessive toxicity. 6 In a univariate analysis related to age, this study revealed no significant difference in CR between the different age groups, and the results suggest that the MIDAM regimen could be an acceptable choice as salvage treatment in the elderly. Induction-related death was linked to performance status, with no significant influence of age.…”
mentioning
confidence: 59%